Lessons Learned – the Learning Curve of Percutaneous Hallux Valgus Correction Using 3rd Generation MICA in 106 Consecutive Cases - Andreas Kurt Toepfer MD, PhD (Foot & Ankle Orthopaedics, 2023)
Category: Bunion; Other Introduction/Purpose: Minimally-invasive Chevron and Akin osteotomy (MICA) represents the third-generation percutaneous hallux valgus surgery which is characterized by an extra-articular osteotomy, stable internal fixation and a high potential for correction. Compared to other percutaneous techniques of the foot, MICA is generally regarded as an advanced and demanding surgical procedure with a prolonged learning curve. The aim of this study is to analyze a single-surgeons learning curve with his first 106 consecutive MICA procedures. Methods: Between May 2018 and November 2022, 106 consecutive MICA procedures performed by the author were prospectively analyzed focusing on surgery duration, number of fluoroscopies, radiological correction results and surgery- associated complications using a modified Clavien-Dindo classification. There were 95 female and 11 male patients with a mean age of 53y (range 16-78y). The mean preoperative intermetatarsal angle I/II (IMA) was 15,7°, the mean hallux valgus angle (HVA) 28,7°. Results: The average amount of radiological correction was 12,6° for IMA and 16,8° for HVA. Overall, the mean surgery duration was 41,6min. (range 27-90min.), the number of fluoroscopies (fs) was 110,8 (range 64-186 fs). Comparing the first 10 MICAS vs. the last 10 procedures, both surgery duration and the amount of fluoro shots decreased significantly (58,8min vs. 32,4min and 165,9 fs vs. 83,1fs). According to the modified Clavien-Dindo classification, there were three grade 1 complications (superficial cellulitis requiring oral antibiotics), four grade 2 complications (1 intraoperative conversion to open surgery, 1 delayed union, 2 symptomatic recurrences) and one grade 3 complication (delayed wound-healing requiring superifical wound revision). Overall screw removal rate was 18 /106 cases, all due to prominent hardware with square headless designed screws (non-beveled). Conclusion: This study represents the largest case series on the learning curve of MICA. Although the learning curve is prolonged requiring specific training and intensive practice, the rate of severe complications is not increased compared to open hallux valgus surgery. The use of bevel-headed screws is strongly advised to reduce the rate of secondary hardware removal. The learning curve manifests itself predominantly in a decreasing operation time and lower number of fluoroscopies. Adherence to the principles of MICA with stable fixation and meticulous intraoperative control of each surgical step helps to reduce complications and allows for adequate correction from the beginning.